Pharmacokinetics Of Oxytetracycline In The Swamp Buffalo (Bubalus Bubalis) - Hashim, Kalthum (1984)
Pharmacokinetics of oxytetracycline (OTC) was studied in swamp mg/kg buffalo heifers and cows after a single injection of OTC hydrochloride intravenously and OTC long acting 20 (LA) formulation (Terramycin/LA, Pfizer) intramuscularly using a crossover study. The concentration of OTC in serum samples was measured by a bioassay technique using Bacillus cereus (ATCC 11778) as the test organism. The disposition curve for oxytetracycline activities after intravenous administration was best described by a two-compartment open model. The serum concentrations at time zero, co'p, for buffalo cows and buffalo heifers were 61 . 37+19 . 62 mcg/ml and 33 . 09+9 . 93 mcg/ml respectively . The elimination half-lives for buffalo cows (10.13+2 . 72 h) and heifers ( 8.72+2.14 h) after intravenous injection of the drug were not significantly different ( P)0.05). The apparent volume o f distribution was significantly higher in buffalo cows ( 2.84+0 . 46 L/kg) than in heifers ( 2.0+0.42 L/kg ) but the total body clearance did not differ significantly (P>0 . 05) . Following a single intramuscular injection of OTC-LA formulation only one rate constant of absorption was noted in buffalo cows (ka1-0. 05 h) but two rate constants of absorption were noted for heifers - a fast rate ( ka1-3 . 62 h) and a slow rate ( ka2 -0. 04 h). The peak serum concentration of OTC for buffalo cows was 4 . 56+1 . 48 mcg/ml at 4.67+1.91 hours and for buffalo heifers was 4.40+ 0.57 mcg/ml at 1.67+0.26 hours.The bioavailability of OTC was 64 and 24 per cent for buffalo cows and heifers respectively . Plasma concentrations above 0.5 mcg/ml were maintained for approximately 50-60 hours . The minimum inhibition concentration (MIC) for eleven isolates from diseased buffaloes ranged from 0 . 25 to 4.0 mcg/ml . For the swamp buffalo OTC-LA is recommended at a dosing rate of 20 mg/kg injected intramuscularly at 48-hour dosage intervals for highly susceptible organisms (MIC<1 mcg/m1 ) . However it is preferable to use the conventional OTC formulation intramuscularly for less susceptible organisms (MIC>2 mcg/ml ) .